AN ANALYSIS OF STUDENTS' ABILITY IN WRITING ENGLISH TEXTS AT THE ELEVENTH GRADE STUDENTS OF MAN 2 LUBUKLINGGAU - Sari Pitri, Deliya; Triyogo, Agus; Oktaviani, ayu (LP3MKIL, 2023)
The objective of this study was to find out students' ability in writing English texts. This study used the descriptive qualitative method and data collected in writing analytical exposition text. The population in this study was the eleventh-grade students of MAN 2 Lubuklinggau. The subject of this study was XI IPA 4 considered 32 students who took a class by using purposeful sampling. Based on the result of the writing analytical exposition text the eleventh-grade students of MAN 2 Lubuklinggau were in “Good Criteria”. The writer used five elements of writing for analyzing students’ ability in writing English text. First was students’ ability in content, there were 14 students with “Very Good”, 16 students with “Good”, and 2 students with “Fair”. Second was students’ ability in organization, there were 11 students “Very Good”, 19 students “Good”, and 2 students “Fair”. Third was students’ ability in vocabulary, there were 3 students with “Very Good”, 15 students with “Good”, and 14 students with “Fair”. Fourth was students’ ability in language use, there were 26 students “Very Good” and 6 students “Good”. Fifth was students’ ability in mechanics, there were 22 students “Very Good” and 10 students “Good”.